Sistem Kontrol Torsi pada Motor DC - Arifin Wahid Ibrahim; Triyogatama Wahyu Widodo; Tri Wahyu Supardi (IJEIS (Indonesian Journal of Electronics and Instrumentation Systems), 2016)
The use of a DC motor in the industrialized world is very important. Speed of DC motor and torque of DC motor greatly affects quality and quantity of product. Therefore, we need control system of a DC motor that can be set speed and torque. The number of industry players complained about damage to the DC motor because transported load torque of motor exceeds capabilities of torque of DC motor. Based on these problem, we should make torque control system in DC motor.Torque control system made by regulating armature current of DC motor separately excited with current field  constant condition. Torque control system consist of speed control and current control, namely control system two level. Output signal speed control system will be the current reference signal.Testing has been carried out with a maximum load of 3690 grams and a nominal current of 0.8 A or nominal torque of 0.323 Nm. The results shows the effective torque of motor is able to be set in the range of 0.182 Nm - 0,243 Nm. Expected to value effective of regulated torque is able to withstand infinite heavy loads without damaging the motor.